INTERPRETASI MAKNA SULHU DALAM PENYELESAIAN KASUS NUSYUZ SUAMI PERSPEKTIF TAFSIR - Syafi’i; Mochammad Novendri S (University of Islam Malang, 2024)
In Islamic law domestic conflict is referred to by the term nusyuz. The concept was taken from the Q.S. An-Nisa': 34 and 128. From this verse, when a comparison is made between the wife's nusyuz settlement and the husband, there is a difference in settlement pattern, both of which indicate discrimination against the wife. Therefore, it is necessary to examine the meaning of the sulhu in depth by interpreting the meaning of the sulhu in the settlement of the case from the nusyuz husband's interpretation perspective. This study used the content analysis method, a research technique to draw conclusions from legitimate data by considering the context. As for the results of this study, the reason for using the word